Moving to Keep Fit: Feeding Behavior and Movement of Helicoverpa armigera (Lepidoptera: Noctuidae) on Artificial Diet With Different Protein: Carbohydrate Ratios. Issue 5 (26th October 2019) - Wang, Peng; Furlong, Michael J; Walsh, Thomas K; Zalucki, Myron P
Abstract: Insect herbivores can modify their foraging behavior to obtain a balanced food intake, and they tend to move between food sources with different nutrient values. We investigated this movement in early instar larvae of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) using a putative optimal artificial diet (OP) and high protein (HP) and high carbohydrate (HC) artificial diets based on protein (p) and carbohydrate (c) ratios. Larvae were allowed to choose between the same kind of diet cubes (effectively no-choice), or diet cubes with different p: c ratios. In no-choice tests, we found that first instar larvae remained longest on OP diet and spent the least time on HC diet, while third instar larvae remained longest on HC diet and spent least time on OP diet. First instar larvae moved the most when provided with HC diet, while third instar larvae moved most when provided with OP diet. However, both stages moved the least when allowed to choose between diet cubes with different p: c ratios. The relative growth rate decreased when larvae increased their movement, but this influence was not evident when larvae fed on HC diet. Larvae that fed only on HC diet had the highest relative growth rate, followed by larvae with access to all diets simultaneously, indicating a behavior to mix nutrient intake. We relate these findings to behavior of this major pest species under field conditions.